Communication Using Celebrities in the Non-Profit Sector: Case Study of BAZNAS - Nadifa Nur Aliza SHAFIRA; N.I.S PUTRI (Communications of International Proceedings, 2020)
The use of celebrities to alert people about social causes is currently a popular marketing technique used by non-profit organizations, and philanthropy becoming a trend for the younger generation gave the spotlight for non-profit organizations to do social campaigns, especially campaigns using celebrities. Therefore, this research intent is to know how effective communication using celebrities in the non-profit sector. This research discusses Celebrity Credibility, Entity Credibility, Attitude Towards Ad, Behavioural Intentions, Perceived Fit, General Fit, Motivation Attribution, Attitude Towards Celebrity being used in communication using celebrities. Structural Equation Modelling using Lisrel 8.8 was used to analyze communication effectiveness using a celebrity in the non-profit sector. The research result shows that Attitude Towards Ad and Entity Credibility influences Behavioural Intentions, Entity Credibility, and Celebrity Credibility influences Attitude Towards Ad, Motivation Attribution along with Perceived Fit influences Celebrity Credibility, Perceived Fit influences Motivation Attribution, and Perceived Fit is being influenced by Attitude Towards Celebrity and General Fit.
Keywords: Attitude Towards Ad; Motivation Attribution; Attitude Towards Celebrity; Non-Profit Sector.